2019
DOI: 10.1002/acn3.723
|View full text |Cite
|
Sign up to set email alerts
|

Grades of brain arteriovenous malformations and risk of hemorrhage and death

Abstract: Objective To assess the relationship of the grade of unruptured and untreated Brain Arteriovenous Malformations (AVMs), with the risk of subsequent stroke and death during follow‐up. Methods This prospective study was drawn from a cohort of adult patients with unruptured AVMs, who participated in the conservative treatment arm (medical management only for headache or seizures) of the randomized clinical trial of unruptured brain AVMs (ARUBA study). The grade of AVMs (Spetzler–Martin scale) was dichotomized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…23 No formal detailed guidelines on the management of unruptured brain AVM have emerged from professional associations. Two consensus reports endorsed by the American Heart Association, the first from 2001 cited that treatment results vary considerably 24 and the most recent from 2017 that medical management alone and three often complementary methods of interventional therapy exist. 25 In summary, after mean length of follow-up 50•4 months (SD±22•9; median 48•0, IQR 35•9-71•1), medical management alone remained superior to medical management with interventional therapy for the prevention of death or symptomatic stroke in patients with an unruptured brain arteriovenous malformation in the ARUBA trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 No formal detailed guidelines on the management of unruptured brain AVM have emerged from professional associations. Two consensus reports endorsed by the American Heart Association, the first from 2001 cited that treatment results vary considerably 24 and the most recent from 2017 that medical management alone and three often complementary methods of interventional therapy exist. 25 In summary, after mean length of follow-up 50•4 months (SD±22•9; median 48•0, IQR 35•9-71•1), medical management alone remained superior to medical management with interventional therapy for the prevention of death or symptomatic stroke in patients with an unruptured brain arteriovenous malformation in the ARUBA trial.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although outcomes in the medical arm were infrequent, and few patients with Spetzler-Martin Grade III to IV AVMs were randomised in ARUBA, a recent analysis of the original ARUBA data failed to show an association between haemorrhage rate and lesion size among patients in the medical management arm. 24 The declining slope of haemorrhage events in the Kaplan-Meier curves over the 10-year follow-up for those presenting without haemorrhage in the observational Multicentre Arteriovenous malformation Research Study (MARS) also suggests that the risk of rupture in unbled patients may subside over time. 25 How some lesions seem stable for decades or life-time is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found less impaired outcomes in the SM I and II group compared to SM III-V [ 15 ]. Stefani et al found no association in the ARUBA trial between risk of stroke or death and the SM grade of the AVM in the medical arm, prompting a call for further study into which unruptured AVMs present the highest risk of hemorrhage [ 16 ].…”
Section: The Aruba Trialmentioning
confidence: 99%
“…Hemorrhage frequency depends on the characteristics of the AVM, such as lesion size. With brain AVM, hemorrhage reportedly occurs in about 2%-4% of untreated cases [2]. Endovascular embolization, microsurgery, and radiosurgery have been used to prevent hemorrhage [1,3,4], but no comprehensive reports have clarified the treatment for pelvic AVM.…”
Section: Introductionmentioning
confidence: 99%